Use of Nonprofessionals at Reference Desk - Courtois, Martin P.; Goetsch, Lori A. (My University, 1984)
The staffing of reference desks by nonprofessionals has been a subject of controversy in academic librarianship. The view that only professional librarians are qualified to provide reference service has been challenged by the fact that nonprofessionals are being used and can effectively answer many patron queries. Several key studies have explored both the practical and theoretical implications of this use of, nonprofessionals. Bunge's research (1967) on the relationship between library education and reference efficiency demonstrated no significant difference between nonprofessional and professional performance in answering questions accurately, although professionals took significantly less time to answer queries.
Citation: Courtois, Martin P. and Lori A. Goetsch, “Use of Nonprofessionals at Reference Desk,” College and Research Libraries 45(5): 385-391, September 1984.
Keywords: Information Science; Library Reference; Nonprofessionals